Passage of the barnacle goose through the Baltic area - Kumari, Erik (Wildfowl, 1971)
The Barnacle Goose Branta leucopsis is a numerous transit migrant on the west coast and islands of Estonia (particularly in the spring). Mass halting places in the same localities have been known to local residents for at least 150 years. In earlier times the geese were hunted from hides, but nowadays hunting has been banned and its mass halting places have been put under state protection. The greatest numbers occur during the first twenty days of May when up to 10,000 individuals are present. At the same time every spring, a similar number can be recorded in regular halting places in the vicinity of Gotland Island (Sweden). The whole population nesting in Novaya Zemlya and Vaigach Island, and wintering in the Netherlands, passes through these two areas. The autumn migration is dispersed and the birds do not halt for any considerable time. During the last ten years a constant increase in numbers has been observed, owing primarily to the breeding success. The species has not been sufficiently studied in the nesting areas and very little is known about migration to the north-east of Estonia. It is necessary to continue the study of the biology, migration and distribution of the Barnacle Goose as well as to guarantee the protection of the species all the year round, in nesting and wintering areas.